Negotiating the Joint Career: Couples Adapting to Alzheimer's and Aging in Place - Renée L. Beard; Sasha Sakhtah; Vanessa Imse; James E. Galvin (Journal of Aging Research)
To understand the impact of memory loss on aging in place, this paper investigated dyads where one spouse had been diagnosed with memory loss. In-depth qualitative interviews were conducted with ten couples (N=20). Grounded theory methods were used to collect, code, and analyze data into themes. Data revealed consensus among and between dyads that it was best to focus on living, rather than what had been or might someday be lost. Nonetheless, differences according to gender and cognitive status (e.g., diagnosed or spouse) were reported. Given population aging, identifying the impact of gender roles and social norms on the potential for aging in place with memory loss is critical. Community services and care practices must be sensitive to the ways that couples prioritized and organized their relationship prior to diagnosis in order to encourage positive patterns of care between couples, foster successful adaptation to changing needs, and support in-home arrangements as long as possible.